Subsurface imaging of flexible circuits via contact resonance atomic force microscopy - Wang, Wenting; Ma, Chengfu; Chen, Yuhang; Zheng, Lei; Liu, Huarong; Chu, Jiaru (Beilstein Journal of Nanotechnology, 2019)
Subsurface imaging of Au circuit structures embedded in poly(methyl methacrylate) (PMMA) thin films with a cover thickness ranging from 52 to 653 nm was carried out by using contact resonance atomic force microscopy (CR-AFM). The mechanical difference of the embedded metal layer leads to an obvious CR-AFM frequency shift and therefore its unambiguous differentiation from the polymer matrix. The contact stiffness contrast, determined from the tracked frequency images, was employed for quantitative evaluation. The influence of various parameter settings and sample properties was systematically investigated by combining experimental results with theoretical analysis from finite element simulations. The results show that imaging with a softer cantilever and a lower eigenmode will improve the subsurface contrast. The experimental results and theoretical calculations provide a guide to optimizing parameter settings for the nondestructive diagnosis of flexible circuits. Defect detection of the embedded circuit pattern was also carried out, which indicates the capability of imaging tiny subsurface structures smaller than 100 nm by using CR-AFM.
Keywords: atomic force microscopy (AFM); contact resonance atomic force microscopy (CR-AFM); contact stiffness; defect detection; flexible circuits; subsurface imaging

(untitled) - Shakir, I.; Ali, Z.; Bae, J.; Park, J.; Kang, D. J. (Nanoscale, 2014)

(untitled) - Liu, L.; Ye, D.; Yu, Y.; Liu, L.; Wu, Y. (Carbon, 2017)

(untitled) - Shakir, I.; Shahid, M.; Cherevko, S.; Chung, C.-H.; Kang, D. J. (Electrochim. Acta, 2011)

(untitled) - Kurra, N.; Hota, M. K.; Alshareef, H. N. (Nano Energy, 2015)

(untitled) - Cheong, H.-G.; Song, D.-W.; Park, J.-W. (Microelectron. Eng., 2015)

(untitled) - Khan, U.; Kim, T.-H.; Lee, K. H.; Lee, J.-H.; Yoon, H.-J.; Bhatia, R.; Sameera, I.; Seung, W.; Ryu, H.; Falconi, C.; Kim, S.-W. (Nano Energy, 2015)

(untitled) - Xu, T.; Miao, J.; Li, H.; Wang, Z. (Nanotechnology, 2009)

(untitled) - Yu, S.; Wang, S.; Lu, M.; Zuo, L. (Sens. Actuators, A, 2017)

(untitled) - Liu, G.; Tan, Q.; Kou, H.; Zhang, L.; Wang, J.; Lv, W.; Dong, H.; Xiong, J. (Sensors, 2018)

(untitled) - Lee, C.-Y.; Chiang, Y.-C.; Weng, F.-B.; Li, S.-C.; Wu, P.-H.; Yueh, H.-I. (Renewable Energy, 2017)

(untitled) - Sahatiya, P.; Puttapati, S. K.; Srikanth, V. V. S. S.; Badhulika, S. (Flexible Printed Electron., 2016)

(untitled) - Lee, C.-Y.; Chuang, S.-M.; Lee, S.-J.; Hung, I.-M.; Hsieh, C.-T.; Chang, Y.-M.; Huang, Y.-P. (Sens. Actuators, A, 2015)

(untitled) - Rabe, U.; Arnold, W. (Ann. Phys. (Berlin, Ger.), 1994)

(untitled) - Rabe, U.; Janser, K.; Arnold, W. (Rev. Sci. Instrum., 1996)

(untitled) - Mazeran, P.-E.; Loubet, J.-L. (Tribol. Lett., 1999)

Applied Scanning Probe Methods - Rabe, U. (Atomic Force Acoustic Microscopy, 2006)

(untitled) - Passeri, D.; Reggente, M.; Rossi, M.; Nunziante Cesaro, S.; Guglielmotti, V.; Vlassak, J. J.; de Francesco, A. M.; Scarpelli, R.; Hatipoğlu, M.; Ajò, D. (Eur. J. Mineral., 2016)

(untitled) - Wagner, R.; Moon, R. J.; Raman, A. (Cellulose, 2016)

(untitled) - Marinello, F.; Pezzuolo, A.; Carmignato, S.; Savio, E.; Chiffre, L. D.; Sartori, L.; Cavalli, R. (AIP Conf. Proc., 2015)

(untitled) - Natali, M.; Passeri, D.; Reggente, M.; Tamburri, E.; Terranova, M. L.; Rossi, M. (AIP Conf. Proc., 2016)

(untitled) - Tsuji, T.; Yamanaka, K. (Nanotechnology, 2001)

(untitled) - Parlak, Z.; Levent Degertekin, F. (J. Appl. Phys., 2008)

(untitled) - Ma, C.; Chen, Y.; Arnold, W.; Chu, J. (J. Appl. Phys., 2017)

(untitled) - Wang, T.; Ma, C.; Hu, W.; Chen, Y.; Chu, J. (Microsc. Res. Tech., 2017)

(untitled) - Piras, D.; Sadeghian, H. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Cadena, M. J.; Chen, Y.; Reifenberger, R. G.; Raman, A. (Appl. Phys. Lett., 2017)

(untitled) - Killgore, J. P.; Kelly, J. Y.; Stafford, C. M.; Fasolka, M. J.; Hurley, D. C. (Nanotechnology, 2011)

(untitled) - Kimura, K.; Kobayashi, K.; Matsushige, K.; Yamada, H. (Ultramicroscopy, 2013)

(untitled) - Dimitriadis, E. K.; Horkay, F.; Maresca, J.; Kachar, B.; Chadwick, R. S. (Biophys. J., 2002)

(untitled) - Fabrikant, V. I. (ZAMP, 2006)

(untitled) - Schwarzer, N. (J. Tribol., 2000)

(untitled) - Batog, G. S.; Baturin, A. S.; Bormashov, V. S.; Sheshin, E. P. (Tech. Phys., 2006)

(untitled) - Yoffe, E. H. (Philos. Mag. Lett., 1998)

(untitled) - Constantinescu, A.; Korsunsky, A. M.; Pison, O.; Oueslati, A. (Int. J. Solids Struct., 2013)

(untitled) - Korsunsky, A. M.; Constantinescu, A. (Thin Solid Films, 2009)

(untitled) - Stan, G.; Adams, G. G. (Int. J. Solids Struct., 2016)

(untitled) - Perriot, A.; Barthel, E. (J. Mater. Res., 2004)

(untitled) - Doerner, M. F.; Nix, W. D. (J. Mater. Res., 1986)

(untitled) - Stan, G.; Mays, E.; Yoo, H. J.; King, S. W. (Nanotechnology, 2016)

(untitled) - Hurley, D. C.; Turner, J. A. (J. Appl. Phys., 2007)

(untitled) - Ma, C.; Chen, Y.; Chen, J.; Chu, J. (Appl. Phys. Express, 2016)

(untitled) - Kopycinska-Müller, M.; Geiss, R. H.; Hurley, D. C. (Ultramicroscopy, 2006)

(untitled) - Sharahi, H. J.; Shekhawat, G.; Dravid, V.; Park, S.; Egberts, P.; Kim, S. (Nanoscale, 2017)

(untitled) - Stan, G.; King, S. W.; Cook, R. F. (Nanotechnology, 2012)

(untitled) - Guzman, H. V.; Garcia, R. (Beilstein J. Nanotechnol., 2013)

(untitled) - Vilhena, J. G.; Pimentel, C.; Pedraz, P.; Luo, F.; Serena, P. A.; Pina, C. M.; Gnecco, E.; Pérez, R. (ACS Nano, 2016)

(untitled) - Steiner, P.; Roth, R.; Gnecco, E.; Glatzel, T.; Baratoff, A.; Meyer, E. (Nanotechnology, 2009)